FOOD AND FEEDING ACTIVITY OF ILISHA MEGALOPTERA LARVAE IN SHATT AL-ARAB ESTUARY - AHMED, S.M.; AL-OKAILEE, M.T.; HUSSAIN, N.A. (Iraqi Journal of Aquaculture, 2022)
The guts of 110 specimens of Ilisha megaloptera larvae ranging in length between 6-21mm were examined. The study showed that I. megaloptera in the larval stage is phytoplankton feeders, consume mainly centric and pinnate diatoms, with centric diatoms being more important that pinnate especially in the smaller size larvae. Spatial and seasonal variations showed that there were no differences in the incidence of feeding during the survey in all stations sampled. This study showed that larval I.megaloptera appear to select food of a certain type (diatoms), which do not vary with the larval size.